DIRECTIVE SPEECH ACTS IN EDITORIALS NARRATIVES OF THE JAKARTA POST - Muhammad Hanif Nooralam; Hayatul Cholsy (Prologue: Journal on Language and Literature, 2024)
Directive speech acts function as an invitation or order from the speaker to the interlocutor to perform an activity expected by the first speaker. Directive speech acts can be seen through editorials written by media editors in newspapers, such as the online mass media The Jakarta Post. The purpose of this study is to find the function of directive speech acts contained in the editorial narratives of The Jakarta Post. The research data comes from editorial narratives of The Jakarta Post published in September-October 2023. Based on the analysis, it is found that indirect directive speech acts in the form of declarative sentences most often dominate. The most dominant function is reminding, followed by requesting and suggesting. Furthermore, there is the function of demanding, while the functions of ordering and recommending are rarely used. The conclusion of the research shows that The Jakarta Post online mass media tends to use a more subtle and persuasive approach in conveying messages to targeted readers or speech partners.